Sociology Review of Social Phenomenon, Social Rules and Social Technology - Dadang Hartanto (Budapest International Research and Critics University, 2020)
Law is a rule that was born, lived and developed in the midst of society. There are laws that come from religious norms or norms that originate from God; norms or rules of decency originating from the hearts of human beings; norms or rules of politeness, that is the rules of life arising from association, the interaction of human groups in society and regulating human behavior towards other humans; as well as legal norms or rules that are rules made by the authorities whose contents are binding on everyone and their implementation can be defended by force by state instruments. Because the law is very urgent, it must be as flexible as possible. The law must be able to adjust to the dynamics of people's lives very quickly, because of the development of science and technology. Law is very or even must be able to deal with various changes that exist. If they are unable, the people as legal subjects will lose faith in the law. This paper talks about law as a social phenomenon of social principles and social technology in the lens of legal sociology.